Antioxidant and Antifatigue Properties of the Aqueous Extract of Moringa oleifera in Rats Subjected to Forced Swimming Endurance Test. (19th January 2016) - Lamou, Bonoy; Taiwe, Germain Sotoing; Hamadou, André; Abene,; Houlray, Justin; Atour, Mahamat Mey; Tan, Paul Vernyuy
Abstract : The effects of the aqueous extract of Moringa oleifera on swimming performance and related biochemical parameters were investigated in male Wistar rats (130–132 g). Four groups of rats (16 per group) were fed a standard laboratory diet and given distilled water, 100, 200, or 400 mg/kg of extract, respectively, for 28 days. On day 28, 8 rats from each group were subjected to the forced swimming test with tail load (10% of body weight). The remaining 8 rats per group were subjected to the 90-minute free swim. Maximum swimming time, glycemia, lactamia, uremia, triglyceridemia, hepatic and muscle glycogen, hematological parameters, and oxidative stress parameters (superoxide dismutase, catalase, reduced glutathione, and malondialdehyde) were measured. Results . M. oleifera extract increased maximum swimming time, blood hemoglobin, blood glucose, and hepatic and muscle glycogen reserves. The extract also increased the activity of antioxidant enzymes and decreased the blood concentrations of malondialdehyde. Furthermore, it decreased blood concentrations of lactate, triglycerides, and urea. In conclusion, the antifatigue properties of M. oleifera extract are demonstrated by its ability to improve body energy stores and tissue antioxidant capacity and to reduce the tissue build-up of lactic acid.